2021
DOI: 10.1101/2021.02.18.21252033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient prioritisation methods to shorten waiting times for elective surgery: a systematic review of how to improve access to surgery

Abstract: Background: Concern about long waiting times for elective surgeries is not a recent phenomenon, but it has been heightened by the impact of the COVID-19 pandemic and its associated measures. One way to alleviate the problem might be to use prioritisation methods for patients on the waiting list and a wide range of research is available on such methods. However, significant variations and inconsistencies have been reported in prioritisation protocols from various specialties, institutions, and health systems. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Average wait-time is a key measure to gauge the performance of prioritization of waitlist (Rahimi et al, 2017;Rana et al, 2022;Rathnayake et al, 2021;Silva-Aravena et al, 2021). It can be seen that MCDM techniques reduce the average waiting time and as compared to WSM, Fuzzy TOPSIS technique (proposed in this research) has not only reduced it further but also substantially reduce maximum wait-time and number of delayed surgeries.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Average wait-time is a key measure to gauge the performance of prioritization of waitlist (Rahimi et al, 2017;Rana et al, 2022;Rathnayake et al, 2021;Silva-Aravena et al, 2021). It can be seen that MCDM techniques reduce the average waiting time and as compared to WSM, Fuzzy TOPSIS technique (proposed in this research) has not only reduced it further but also substantially reduce maximum wait-time and number of delayed surgeries.…”
Section: Discussionmentioning
confidence: 80%
“…Patients' prioritization is a process of ranking patients based on the important or significant factors (Déry et al, 2020;Rathnayake et al, 2021). After referral, a specialist examines and evaluates the patients' health condition and decides the priority to perform the relevant procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This review assesses the effects of perioperative time-management methods on waiting times of patients for elective surgeries as one of the sub-reviews in a portfolio of systematic reviews conducted with a broader search to support a holistic approach to nding solutions for long waiting times for elective surgery (19,20). The portfolio review was registered in PROSPERO (CRD42019158455) and the review is reported here according to the PRISMA 2009 statement and checklist (21).…”
Section: Methodsmentioning
confidence: 99%
“…It is vital that healthcare systems appropriately prioritise surgeries to reduce the impact of health complications from long surgery waiting times (Rathnayake, Clarke, & Jayasinghe, 2021).…”
Section: E) Deaths Waiting For Surgerymentioning
confidence: 99%